PERSPEKTIF USHUL FIQIH ATAS ZAKAT PROFESI DALAM PEMIKIRAN FIQIH KONTEMPORER - Rohmah, Yuni; Setiawan, Hendrik; Mubarriroh, Lailatul; Mamdukh, Muhammad; Latifah, Eny (JITAA : Journal Of International Taxation, Accounting And Auditing, 2023)
The purpose of this research is to find out the perspective of ushul fiqh scholars on professional zakat in contemporary fiqh thinking. The research method used is descriptive qualitative with the type of literature. The results of the study are that there are differences of opinion among contemporary scholars about the amount of professional zakat, namely 2.5% and 20%. Opinion of professional zakat with a level of 2.5%, this is because it is based on qiyas (analogous) to trade zakat. The reason is because professional workers are selling services, thus including tijarah (trade). Professional zakat is calculated based on hawl or not based on hawl. If it is based on hawl, what is subject to zakat is the accumulation (sum) of income for one year. If it is not based on hawl, then the obligation of zakat is carried out when the income reaches the nishab